PENGARUH UKURAN PARTIKEL, WAKTU DAN SUHU PADA EKSTRAKSI FENOL DARI LENGKUAS MERAH - Rondang Tambun; Harry P. Limbong; Christika Pinem; Ester Manurung (Talenta Publisher (Universitas Sumatera Utara), 2016)
Galangal is one of spices containing phenol. This study aims to product phenol in a liquid phase from galangal. The variations performed in this study involve the time of extraction (3 hours, 6 hours, 9 hours), temperature (30 oC, 45 oC, 60 oC) and particle size of raw material (70 mesh, 100 mesh, 140 mesh). One of the analysis in this study is the yield of phenol. The highest phenol in this study is about 4,5%. This result is obtained using 140 mesh of tray at 60°C of temperature and 9 hours of extraction time.